DETERMINAN KEPEMILIKAN TABUNGAN KELUARGA DI KABUPATEN PANGKEP - samsu gaffar (Media Mahardhika, 2022)
This study was conducted to determine the factors that influence the ownership of family savings in Pangkep Regency by analyzing the effect of the variables of the number of family members, the education level of the head of the family, and the employment status of the head of the family on the ownership of family savings using the multiple linear regression analysis methods. The data used is the result of the 2021 family data collection in Pangkep Regency which was taken using the documentation technique presented by the district. The results of this study indicate that based on a partial analysis of the variable Number of Family Members (X1) and the variable of the education level of the head of the family (X2)  does not affect the variable of Family Savings Ownership in Pangkep Regency (Y). Meanwhile, the variable Job Status of the Heads of Families (X3) affects the variable of Family Savings Ownership in Pangkep Regency (Y). For simultaneous analysis, the independent variable (variable X) affects the dependent variable of Family Savings Ownership in Pangkep Regency (variable Y).